Al(OTf)3: An Efficient Lewis Acid Additive for Domino Addition–Elimination of Grignard Reagents to Activated Ketones - Pieterse, Tanya; Visser, Melanie; Marais, Charlene; Bezuidenhoudt, Barend C. B. (Synlett, 2016)
It has been demonstrated that aluminium triflate in either stoichiometric or catalytic quantities facilitates the addition–elimination of Grignard reagents to electron-rich ketones, such as methoxy substituted acetophenones, propiophenone and chromanone in a one-pot process, and that it has an enhancing effect on the addition of these reagents to the ketones. It has also been found that the reactions are highly stereoselective towards one regioisomer of the alkene in the case of oxygenated aryl-alkyl substituted substrates, but not when the elimination originates from a double benzylic alcohol intermediate.
Keywords: aluminium triflate; Grignard reagent; ketone; olefin; addition–dehydration; one-pot reaction